Investigation of underwater sound wave propagation characteristics for channel modelling - Umamaheswararao, S.; N V S S Kumar, M.; Madhu, R (International Journal of Engineering and Technology, 2019)
Unlike terrestrial communication which is based on radio communication principle, sound is the means of communication in underwater. This is because sea water conducts electricity pretty well, and anything that conducts electricity will absorb the electromagnetic energy of the radar and not allow it to penetrate. The dielectric constant of water is not good for RF propagation. However water is good for propagating sound wave though it propagates much slower than the RF waves. The distance that sound waves (which is a pressure waves) travel is vastly longer than Radio Waves in water. In underwater medium the propagation of sound is effected by characteristics such as velocity of sound wave, sound pressure and sound power, transmission loss of sound in underwater environment, sound absorption in sea water, viscosity, ionic relaxation and scattering. Sound waves while propagating underwater they get attenuated due to cylindrical and spherical spreading of the energy. In this paper, sound wave propagation characteristics are analyzed.Â